The Kings of Big Spring: God, Oil, and One Family's Search for the American Dream - Mealer, Bryan (New York : Flatiron Books, 2018)
Traces the story of the authors family, whose fortunes and prospects became subject to the Texas oil boom of the 1980s and its related glamour, corruption, drug affiliations, and risks.
Keywords: Mealer, Bryan -- Family; Petroleum industry and trade -- Texas; Biography; Big Spring (Tex.); Biography; Texas; Biography; Biographies